The Relationship between Body Mass Index (BMI) and VO2Max in Sports Students - Resti Nurpratiwi; Susi Susanti; Nur Luthfiatus Solikah; Tita Rachma Ayuningtyas; Azizati Rochmania; Romadhiyana Kisno Saputri; Isma Nur Azzizah; Rizky Patria Nevangga (Universitas Negeri Surabaya, 2025)
Background: Sports students, often also athletes and coaches, require optimal physical condition and fitness for peak performance and achievement. Maintaining fitness minimizes health risks and boosts exercise efficiency. VO2Max, the maximal oxygen uptake during intense exercise, is a key cardiovascular fitness indicator closely tied to muscle work capacity. Elevated Body Mass Index (BMI) and excess fat can impair cardiac function, reduce cardiac output, and hinder oxygen uptake, leading to lower VO2Max. This study focuses specifically on trained, active sports students, distinguishing it from prior research on general student populations. Objectives: To examine the relationship between BMI and VO2Max in sports students. Methods: This quantitative descriptive study used an observational analytic design. The study involved a total of 30 subjects active university students (19-22 years) were purposively sampled. BMI was measured with TANITA BC-545N, and VO2Max with the 12-minute Cooper test. Data analysis included descriptive statistics, Shapiro-Wilk normality test, and Pearson correlation. Results: Mean BMI was 21.84 ± 2.52 kg/m². Most participants (70%) had normal BMI; 10% were underweight, 20% overweight. Mean VO2Max was 45.13 ± 4.93 mL/kg/min. Participants VO2Max, 53% were